Compressive Strength Development for Modified Peat using Rubber Crumb (RC) as Reinforcement with Electro-Kinetic Treatment (EKT). - Norazzlina, M. S'adon; Abdul Razak, Abdul Karim; Emilia Evyln, Christermaller; Mohamad Hanif, Mohamad Ariffin; Albert Akun, Merang (Universiti Malaysia Sarawak, 2018)
Peat is classified as an organic soil, with low shear strength and high compressibility behaviour when subjected to the applied loads. In order to allow the construction works on peat, ground improvement techniques are one of the suitable solution to improve the stability of peat and provide a strong sub-grade platform for embankment construction. This research focus on investigating the effects of lightweight waste material; rubber crumb (RC) as reinforcement material mixed homogeneously with peat at 5% cement content, which act as a binder. The size of the RC used is in the range of 5 mm to 8 mm. The peat is categorized as Sapric peat (H7) based on von Post classification which is partially decomposed with recorded moisture content of 425%. The peat is treated with different percentages of RC; 5%, 10% and 15% by dry weight of peat and later the treated peat were applied with the electrokinetic treatment (EKT). The samples are compacted at the optimum moisture content for each design mixture and air-cured for 7, 14 and 28 days for the shear strength development. The Unconfined Compressive Strength (UCS) tests and California Bearing Ratio (CBR) test are performed in order to investigate the strength increment. Due to its lightweight and high durability, it makes rubber crumbs are suitable fiber reinforcement materials to improve peat soil characteristic. The untreated peat is used as control result to compare the strength improvement of the reinforced peat. The application of EKT for 10 minutes duration was practiced with 3.0 V and 12 V for UCS and CBR tests, respectively. The use of RC is as expected due to a good response in the shear strength development after the application of EKT. This finding provides a better understanding of the reinforced peat using RC in improving the engineering behaviour of the peat for construction purposes.